2022
DOI: 10.3390/antibiotics11111487
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Environments as Hotspots of Transferable Low-Level Quinolone Resistance and Their Potential Contribution to High-Level Quinolone Resistance

Abstract: The disposal of antibiotics in the aquatic environment favors the selection of bacteria exhibiting antibiotic resistance mechanisms. Quinolones are bactericidal antimicrobials extensively used in both human and animal medicine. Some of the quinolone-resistance mechanisms are encoded by different bacterial genes, whereas others are the result of mutations in the enzymes on which those antibiotics act. The worldwide occurrence of quinolone resistance genes in aquatic environments has been widely reported, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 280 publications
(278 reference statements)
0
5
0
2
Order By: Relevance
“…This environmental contamination, particularly in marine ecosystems, can exert selective pressure on bacterial communities, fostering the development of antibiotic-resistant strains or the proliferation of resistance genes [ 41 ]. The global presence of quinolone resistance genes in aquatic environments has been extensively documented, especially in areas impacted by urban discharges [ 42 ]. In the Vitória Region, there is frequent deposition of untreated effluents directly into the waters where seafood collection often takes place.…”
Section: Discussionmentioning
confidence: 99%
“…This environmental contamination, particularly in marine ecosystems, can exert selective pressure on bacterial communities, fostering the development of antibiotic-resistant strains or the proliferation of resistance genes [ 41 ]. The global presence of quinolone resistance genes in aquatic environments has been extensively documented, especially in areas impacted by urban discharges [ 42 ]. In the Vitória Region, there is frequent deposition of untreated effluents directly into the waters where seafood collection often takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Significant variations in antibiotic concentrations were observed between different countries and regions, with generally higher FQs levels found in surface water from developing countries compared to developed ones. Notably, surface water in India displayed high concentrations of CIP at 542.45 μg/L [ 26 ] and Kenya at 75.70 μg/L [ 16 ]. The Mediterranean waters of Tunisia exhibited elevated levels of ENR (20.70 μg/L) and NOR (40.20 μg/L) [ 27 ].…”
Section: The Pollution Status Of Fqs In Surface Watermentioning
confidence: 99%
“…Thirdly, discharge from wastewater treatment plants, responsible for handling the treatment of wastewater from urban and industrial areas. However, it is worth noting that complete FQs removal during the treatment process may not always be achieved, resulting in the presence of drug residues in the effluent that can enter the water environment [ 26 , 35 , 37 ]. Gao et al [ 8 ] found that in the Liaohe River Basin in China, the main sources of FQs contamination were wastewater discharge from wastewater treatment plants and agricultural aquaculture.…”
Section: The Pollution Status Of Fqs In Surface Watermentioning
confidence: 99%
See 2 more Smart Citations